2021
DOI: 10.6007/ijarbss/v11-i15/10651
|View full text |Cite
|
Sign up to set email alerts
|

A Concept Paper on Improving Parental Knowledge and Practices on Water Safety and Their Children: A Guide for Drowning Prevention

Abstract: Worldwide, empirical evidence indicate that children are at heightened risk for drowning thus many substantial strategies have been made in understanding childhood drowning. Conversely, in Malaysia the data is scarce and drowning received insufficient attention. To understand the nature of the problem, the mechanism of the events and other indicators related to childhood drowning in Malaysia, a considerable research and programmatic work is required and thus appropriate intervention can be developed. As such, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Morrongiello et al (30) found that, in addition to schools, parents were an especially critical element in the development of adolescents' drowning prevention skills, which was even more apparent in China. Some parental approaches, such as enrolling children in aquatics training, are the most beneficial in helping children develop the water safety knowledge and swimming skills (31). The second most important factor is the financial support.…”
Section: Discussionmentioning
confidence: 99%
“…Morrongiello et al (30) found that, in addition to schools, parents were an especially critical element in the development of adolescents' drowning prevention skills, which was even more apparent in China. Some parental approaches, such as enrolling children in aquatics training, are the most beneficial in helping children develop the water safety knowledge and swimming skills (31). The second most important factor is the financial support.…”
Section: Discussionmentioning
confidence: 99%
“…In Malaysia, based on the 2019 report on causes of death, drowning ranked as one of the top five main factor contributing to the mortality rate among individuals aged 15 -40 years old. In addition, drowning prevention is still a major ignorance because the community thinks drowning is an unavoidable incident (Farizan et al, 2021). There are estimated at least one person dies every day because of drowning incidents in Malaysia but the community is still unaware of the dangers of involving water-based activities (Hariati, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Awareness of the risk of drowning is a signpost on how to spend time next to or in the water without negative consequences. Insufficiency of knowledge and practice on prevention of drowning influence insufficient awareness of the risk of drowning among children (Farizan et al, 2021 ). Many countries are developing plans to reduce drowning.…”
Section: Introductionmentioning
confidence: 99%